2018
DOI: 10.1002/hipo.23037
|View full text |Cite
|
Sign up to set email alerts
|

Spatial object recognition memory formation under acute stress

Abstract: Stress is known to have a critical impact on memory processes. In the present work, we focus on the effects of an acute stress event closely associated to an unrelated learning task. Here, we show that acute stress (elevated platform [EP] session) experienced 1 hr after a weak spatial object recognition (SOR) training, which only induces a short‐term memory (STM), promoted the formation of SOR‐long term memory (SOR‐LTM) in rats. The effect induced by stress was dependent on the activation of glucocorticoid‐ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 56 publications
(77 reference statements)
5
17
0
Order By: Relevance
“…Our results suggest that ERKs1/2 activity is: (1) necessary to induce protein synthesis required for memory formation after retraining and, (2) relevant to set the SOR learning-tag, which marks specific sites activated by re-learning. Finally, and in addition to a great body of evidence showing that the BT process accounts for LTM promotion by novel or stressful experiences 18,38,47 , the present results highlight that the formation of LTM after wSOR retraining is also in line with the assumptions of the BT hypothesis (Fig. 5).…”
Section: Discussionsupporting
confidence: 85%
“…Our results suggest that ERKs1/2 activity is: (1) necessary to induce protein synthesis required for memory formation after retraining and, (2) relevant to set the SOR learning-tag, which marks specific sites activated by re-learning. Finally, and in addition to a great body of evidence showing that the BT process accounts for LTM promotion by novel or stressful experiences 18,38,47 , the present results highlight that the formation of LTM after wSOR retraining is also in line with the assumptions of the BT hypothesis (Fig. 5).…”
Section: Discussionsupporting
confidence: 85%
“…A similar dependence has also been shown for other salient experiences used in behavioral tagging studies. For example, several animal studies and one human experiment reported that postencoding stress improved weakly encoded memories, but impaired strongly encoded ones [96][97][98][99] .…”
Section: Discussionmentioning
confidence: 99%
“…The GR antagonist mifepristone (mife, 20 ng/μl per side) was dissolved in DMSO and diluted in saline for a final concentration of DMSO 5%. The doses were determined from published studies (Korte et al., 1995; Lopes da Cunha et al., 2018; Moncada et al., 2011).…”
Section: Methodsmentioning
confidence: 99%